Comparative analysis of Polymer Electrolyte Membrane (PEM) fuel cells - Balogun, Emmanuel O (Department of Electrical Engineering, 2019)
Per-Fluoro-Sulphonic-Acid (PFSA) ionomers have been singled out as the preferable ionomers for making the Polymer Electrolyte Membrane Fuel Cells (PEMFC) membranes owing to their extensive intrinsic chemical stability and super sulfonic acid strength which is core to the PEMFC proton conductivity. This thesis presents a deeper analysis into these PFSA ionomer membrane electrode assemblies (MEA), presenting an electrochemical-analytical comparative analysis of the two basic types, which are the Long-Side-Chain (LSC) Nafion® and the ShortSide-Chain (SSC) Aquivion® ionomer MEA with emphasis on performance and durability which are currently not well understood. In particular, electrochemical circuit models and semiempirical models were employed to enable distinguishable comparative analysis. Also, in this thesis, we present a further probe into the effect of ionomer ink making processes, critically investigating the effect of the High Share Dispersion (HSD) process on both the Nafion® and Aquivion® ionomer membrane electrode assembly (MEA). The findings in this research provides a valuable insight into the performance and durability of PFSA ionomer membrane under various application criteria. The effect of operating parameters and accelerated stress testing (AST) on the PFSA ionomers was determined using electrochemical impedance spectroscopy (EIS) and electronic circuit model (ECM) analysis. The result of this study, shows that the ionomer ink making process for Nafion® and Aquivion® MEAs are not transferrable. Analysis of the PEMFC performance upon application of the high shear dispersion (HSD) process showed that Nafion® MEA had a 10.47% increase in voltage while the Aquivion® MEA had a 2.53% decrease in voltage at current density of 1.14A/cm2 . Also, upon accelerated stress testing, the Nafion® showed a 10.49% increase in its voltage while the Aquivion® on the other hand had a 7.16% decrease in voltage at 0.66A/cm2 . Thus indicating the HSD process enhances the performance of the Nafion® MEA and inhibits the performance of the Aquivion® MEA.